2020
DOI: 10.1097/scs.0000000000006156
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Epinephrine Mixed With Lidocaine in Plastic Surgery

Abstract: Plastic surgeons commonly administer subcutaneous epinephrine to reduce intraoperative blood loss. The authors hypothesized that there are safe and effective concentration of epinephrine for vasoconstriction and their durations. The aim of this study is to summarize the existing literatures for the usage of epinephrine mixed with lidocaine in plastic surgical field. In 1903, Braun reported that adrenaline prolonged the local anesthetic effects of cocaine. The Parke-Davis Company began selling cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…We have to consider that the optimum safe dose of local anesthetics is more dependent on the route, rate and the site of injection than the drug load. 13 As mentioned before, site and sort of surgery affect optimum concentrations of epinephrine; while in dermatologic plastic surgeries, epinephrine in 1:50,000 concentration is used to reduce the amount of bleeding with satisfying results. 14 The prevalence of cardiovascular toxic adverse effects has been observed to increase in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have to consider that the optimum safe dose of local anesthetics is more dependent on the route, rate and the site of injection than the drug load. 13 As mentioned before, site and sort of surgery affect optimum concentrations of epinephrine; while in dermatologic plastic surgeries, epinephrine in 1:50,000 concentration is used to reduce the amount of bleeding with satisfying results. 14 The prevalence of cardiovascular toxic adverse effects has been observed to increase in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…If epinephrine is more diluted, its characteristics such as onset and time to peak serum concentrations may be influenced and also the duration of action is shortened. 13 …”
Section: Discussionmentioning
confidence: 99%
“…E. Bjornestad and coworkers [29] found 20% and 30% of visceral pain in their study with epidural lidocaine and epidural 2-chloroprocaine respectively, while Yicheng Yang and colleagues [38] found an intraoperative pain incidence ranged at 70% and 47.5% respectively in epidural ropivacaine-morphine and epidural ropivacaine-morphinedexmedetomidine. It is actually known that epinephrine has some properties of antinociceptive and enhances the duration of analgesia used together with LAs [39,40] . Furthermore, recent researches by Aliza Olapour et al [41] said that lidocaine's sensory and motor block were superior to the Ropivacaine's, and epinephrine was found to exert an essential role [39] .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of these epinephrine-local anesthetic combinations has been well studied, leading to well-established guidelines for maximum local anesthetic doses. 1 However, local anesthetics have an associated toxicity risk and prevent impulse transmission/stimulation of motor nerves, which is particularly relevant in peripheral nerve surgery. As an alternative, plain epinephrine may be used to decrease blood loss and minimize blood within the surgical site.…”
mentioning
confidence: 99%
“… 5 A recent review of the literature demonstrated that concentrations of epinephrine between 1:50,000 and 1:400,000 provide superior vasoconstrictive effects compared with dilute epinephrine concentrations. 1 …”
mentioning
confidence: 99%